P176 Patient preferences in steroid resistant ulcerative colitis – a discrete choice experiment survey. (27th May 2021) - Wickramasekera, N; Shackley, P; Coates, E; Barr, A; Lee, M; Blackwell, S; Bedford, H; Dames, N; Sebastian, S; Probert, C; Lobo, A
Abstract: Background: Understanding patient preferences in those who are not responding to steroids for ulcerative colitis is important in informing treatment choices. This study aimed to understand the relative importance of treatment characteristics to patients by conducting a discrete choice experiment (DCE). Methods: Patients completed a two-part online survey. Participants were shown 12 DCE tasks – a series of side by side comparison of competing, hypothetical treatment characteristics describing effectiveness, remission, speed of response, route of administration and safety and asked to select a preferred treatment. Disease control was assessed by the IBD-control-8 questionnaire (poor control < 13). Participants also completed a ranking exercise where patients were asked to rank four commonly used treatments (Adalimumab, Infliximab, Tofacitinib, and Vedolizumab, ) in order of preference. Survey responses were analysed using descriptive statistics and regression analyses. Results: 115 patients completed the survey (mean age 45 years; 52% female; median time since diagnosis 10 years). 107 (93%) had previously received steroids; 81 (70%) thiopurines and 81 (70%) biological therapies or tofacitinib. 51 (45%) reported poor control of ulcerative colitis. Figure 1 shows the results of the regression analyses where all treatment characteristics had a significant influence on patients' treatment choice. Patient preferences were strongest for lower side effects, for example, compared to a treatment that had very common side effects, patients were more likely to take a treatment that had very rare side effects (ß 2.937, p<0.01) even if very rare side effects are usually more severe. Patients preferred a treatment with higher likelihood of induction of response, but they were unable to differentiate between 50% success rate and 60% success rate. Higher levels of remission (ß 0.065, p<0.01) and faster acting treatments were preferred (ß -0.145, p<0.01). Taking a pill daily at home (ß 0.848, p<0.01) or injections at home every 8 weeks (ß0.541, p<0.01) were preferable compared to infusions every 8 weeks. Notably, there was no significant difference between infusion, every 8 weeks at hospital compared to injection, every 2 weeks, at home (ß -0.029, p= 0.85). When asked to rank four commonly used biologics, the most preferred treatment was Infliximab (38%) and Tofacitinib (38%), followed by Vedolizumab (17%) and Adalimumab (6%). Conclusion: Quantifying preferences through DCEs helps to identify and prioritise treatment characteristics that are important to patients. The results could be used to improve discussions between patients and clinicians when reviewing treatment options.